A new iron-nickel-based alloy material and a heat treatment method and application thereof

CN122727652APending Publication Date: 2026-09-11SHANGHAI ELECTRIC POWER GENERATION EQUIPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511759236.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-27
Publication Date
2026-09-11

AI Technical Summary

Technical Problem

[0006]鉴于以上所述现有技术的缺点,本发明的目的在于提供一种新型铁镍基合金材料及其热处理方法和应用,用于解决现有技术中热处理工艺无法有效改善高温合金长期处于高温服役环境下出现负蠕变的问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122727652A_ABST
    Figure CN122727652A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of metallic materials technology, and mainly provides a novel iron-nickel-based alloy material, its heat treatment method, and its application. The heat treatment method includes the following steps: Step 1: solution heat treatment; Step 2: first aging heat treatment; Step 3: second aging heat treatment, followed by holding at the temperature for a period of time and then cooling. This invention achieves full-cycle control of the γ′ phase precipitation process through a combination of single-step solution heat treatment and two-step aging heat treatment, suppressing negative creep in high-temperature alloys during service, avoiding abnormal stress cycles, thermal fatigue, and mechanical fatigue caused by negative creep in structural components, inhibiting the initiation and propagation of cracks in structural components, and improving the service safety and lifespan of high-temperature alloy castings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallic materials technology, and in particular relates to a novel iron-nickel-based alloy material, its heat treatment method, and its application. Background Technology

[0002] Increasing the steam temperature and pressure of ultra-supercritical steam turbines is one of the most effective ways to improve power plant thermal efficiency and reduce coal consumption and carbon emissions. Higher temperatures and pressures mean that key components such as cylinder valve housings are subjected to higher thermal stress, higher creep stress, and more severe oxidation and corrosion, which places higher demands on materials. The application of high-temperature alloys in steam turbine castings is one of the key requirements for the development of advanced ultra-supercritical thermal power generation and high-efficiency gas turbine technologies.

[0003] Currently, the heat-resistant steel materials used in existing power generation units are prone to negative creep during use, causing the castings to shrink and deform contrary to expectations. This dimensional instability drastically increases the tensile stress on bolts in critical sealing areas, potentially leading to bolt overload yielding or creep fracture. Furthermore, the frequent start-ups and shutdowns caused by deep peak shaving in ultra-supercritical turbine units exacerbate thermal and mechanical fatigue issues. The abnormal stress cycles introduced by negative creep, combined with this type of fatigue, will significantly accelerate crack initiation and propagation, posing a major safety hazard.

[0004] Negative creep has been a critical problem plaguing the industry during the long-term service of high-temperature alloys. This phenomenon leads to decreased dimensional stability and deterioration of mechanical properties in alloy materials, and in severe cases, it can even cause equipment failure, greatly affecting the safe application of high-temperature alloys.

[0005] Current heat treatment processes cannot effectively improve the negative creep phenomenon that occurs when high-temperature alloys are subjected to long-term high-temperature service environments, which to some extent limits the further development and application of high-temperature alloy materials. Summary of the Invention

[0006] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a novel iron-nickel based alloy material, its heat treatment method and application, to solve the problem that the heat treatment process in the prior art cannot effectively improve the negative creep of high-temperature alloys under long-term high-temperature service environment.

[0007] To achieve the above and other related objectives, the present invention provides a novel iron-nickel-based alloy material comprising the following components by mass percentage: C 0.03%~0.06%, Si ≤0.2%, Zr ≤0.05%, Cr 16.0%~18.0%, Mo ≤0.9%, Co 1.2%~1.7%, Nb 0.5%~1.2%, Ni 33%~39%, Ti 1.0%~1.5%, Al 0.8%~1.5%, B ≤0.005%, W ≤0.7%, N≤0.01%, Y 0.1%~0.15%, balance Fe and unavoidable impurities.

[0008] In some embodiments of the present invention, the mass percentage of C is 0.03% to 0.05%.

[0009] In some embodiments of the present invention, the mass percentage of Cr is 16.5% to 17.5%.

[0010] In some embodiments of the present invention, the mass percentage of Mo is ≤0.7%.

[0011] In some embodiments of the present invention, the mass percentage of Nb is 0.5% to 1.2%.

[0012] In some embodiments of the present invention, the mass percentage of Ni is 35% to 37%.

[0013] In some embodiments of the present invention, the mass percentage of Ti is 1.1% to 1.4%.

[0014] In some embodiments of the present invention, the mass percentage of Al is 0.9% to 1.2%.

[0015] In some embodiments of the present invention, the total mass percentage of Mo and Nb is 1.0% to 1.5%.

[0016] A heat treatment method for the novel iron-nickel-based alloy material includes the following steps: Step 1, Solution heat treatment: Heat the iron-nickel-based superalloy to 1150 ℃-1190 ℃, hold it at that temperature for 3~5 hours, and then cool it. Step 2, First aging heat treatment: The iron-nickel-based superalloy after solution heat treatment in Step 1 is heated to 620 ℃-660 ℃ and held at that temperature for 20~30 h before cooling. Step 3, Second aging heat treatment: The iron-nickel-based superalloy after the first aging heat treatment in Step 2 is heated to 795 ℃-835 ℃ and held at that temperature for 20~30 h before cooling.

[0017] In some embodiments of the present invention, in step one, the temperature of the solution heat treatment process is 1180 ℃ and the holding time is 3 h.

[0018] In some embodiments of the present invention, in step two, the temperature of the first aging heat treatment process is 650°C and the holding time is 20 h.

[0019] In some embodiments of the present invention, in step three, the temperature of the second aging heat treatment process is 825°C and the holding time is 20 h.

[0020] In some embodiments of the present invention, in step one, the iron-nickel-based superalloy is cooled by air or water.

[0021] In some embodiments of the present invention, in step two, the iron-nickel-based superalloy is cooled by air cooling.

[0022] In some embodiments of the present invention, in step three, the iron-nickel-based superalloy is cooled by air cooling.

[0023] In some embodiments of the present invention, the iron-nickel-based superalloy is heated in a vacuum heat treatment furnace.

[0024] A high-temperature component for an ultra-supercritical steam turbine, the high-temperature component being made of the novel iron-nickel-based alloy material and subjected to the heat treatment method described above.

[0025] As described above, the present invention has the following beneficial effects: This invention combines single-step solution heat treatment with two-step aging heat treatment to adapt to the compositional characteristics of novel iron-nickel-based high-temperature alloys, achieving full-cycle control of the γ′ phase precipitation process. This suppresses the negative creep phenomenon during the service of high-temperature alloys, avoids abnormal stress cycles, thermal fatigue, and mechanical fatigue caused by negative creep in structural components, inhibits the initiation and propagation of cracks in structural components, and improves the service safety and lifespan of high-temperature alloy castings. This invention enables a novel iron-nickel-based high-temperature alloy to possess high high-temperature strength through a heat treatment process, allowing it to maintain good mechanical properties at high temperatures and withstand the dual effects of high temperature and stress. This meets the material strength requirements of high-temperature components in ultra-supercritical steam turbines at temperatures of 650°C and above, ensuring the structural stability of high-temperature components at high temperatures and preventing deformation or damage due to insufficient strength. Attached Figure Description

[0026] Figure 1 The creep curves of the heat-treated iron-nickel-based superalloys in Example 1 and Comparative Example 1 are shown. Figure 2 The creep curves of the heat-treated iron-nickel-based superalloys in Example 2 and Comparative Example 2 are shown. Detailed Implementation

[0027] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.

[0028] The first aspect of this invention provides a novel iron-nickel-based alloy material, comprising the following components by mass percentage: C 0.03%~0.06%, Si ≤0.2%, Zr ≤0.05%, Cr 16.0%~18.0%, Mo ≤0.9%, Co 1.2%~1.7%, Nb 0.5%~1.2%, Ni 33%~39%, Ti 1.0%~1.5%, Al 0.8%~1.5%, B ≤0.005%, W ≤0.7%, N≤0.01%, Y 0.1%~0.15%, balance Fe and unavoidable impurities.

[0029] In some embodiments of the present invention, unavoidable impurities include sulfur (S), phosphorus (P), oxygen (O), hydrogen (H), etc.

[0030] Co can increase the alloying degree of the alloy, enhance the solid solution strengthening effect, and help improve the strength and stability of the alloy at high temperatures, resisting creep deformation.

[0031] Zr and Y can act as grain boundary purifiers, reducing grain boundary energy and improving grain boundary structure and properties. Zr and Y can also form fine oxide particles that pin grain boundaries and inhibit grain boundary sliding, thereby improving the creep resistance of the alloy.

[0032] Trace amounts of boron can fill grain boundary vacancies, enhance grain boundary bonding, reduce the possibility of grain boundary slippage, and thus improve the creep resistance of the alloy.

[0033] Si can improve the surface oxidation resistance of alloys, forming a dense oxide film that protects the alloy matrix from oxidation at high temperatures, thereby indirectly improving the high-temperature stability and creep resistance of the alloy.

[0034] When W dissolves in an iron-nickel matrix, the difference in atomic size causes lattice distortion, increasing the difficulty of dislocations sliding and climbing at high temperatures and reducing the creep deformation rate caused by dislocation movement. At the same time, W has a high melting point, which allows it to remain stably in the matrix for a long time under high-temperature service conditions, avoiding the attenuation of solid solution strengthening effect due to element diffusion, and ensuring that the alloy maintains high matrix strength under long-term high temperatures.

[0035] During alloy smelting and heat treatment, nitrogen (N) rapidly forms fine nitrides with elements such as Nb and Ti, such as NbN and TiN, which exhibit extremely high stability at high temperatures. During smelting, these nitrides hinder the initial growth of austenite grains. During heat treatment, these nitrides pinnate at grain boundaries, limiting further grain coarsening and ultimately resulting in a finer, more uniform grain structure. Grain refinement increases the total area of ​​grain boundaries, dispersing the sliding displacement of individual grain boundaries and thus suppressing negative creep dominated by grain boundary sliding.

[0036] In some embodiments of the present invention, the mass percentage of C is 0.03% to 0.05%. The mass percentage of C can be 0.03%, 0.04%, or 0.05%. C can form a small amount of carbides, which are distributed on the grain boundaries, enhancing the strength of the grain boundaries and inhibiting grain boundary slippage.

[0037] In some embodiments of the present invention, the mass percentage of Cr is 16.5%~17.5%, and the mass percentage of Mo is ≤0.7%. Specifically, the mass percentage of Cr can be 16.5%, 17.0%, or 17.5%, and the mass percentage of Mo can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, or 0.7%. Cr and Mo can dissolve in the iron-nickel matrix to form a solid solution, causing lattice distortion, increasing the resistance to dislocation movement, thereby improving the strength and hardness of the alloy, suppressing dislocation movement, and thus reducing the occurrence of negative creep.

[0038] In some embodiments of the present invention, the mass percentage of Nb is 0.5% to 1.2%. Specifically, the mass percentage content of Nb can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, or 1.2%. Nb can form stable carbides or nitrides, such as NbC and NbN, and can act as a second phase, pinning dislocations and preventing dislocation slippage, thereby playing a precipitation strengthening role and improving the creep resistance of the alloy.

[0039] In some embodiments of the present invention, the mass percentage of Ni is 35% to 37%. Specifically, the mass percentage content of Ni can be 35%, 36%, or 37%.

[0040] In some embodiments of the present invention, the mass percentage of Ti is 1.1% to 1.4%, and the mass percentage of Al is 0.9% to 1.2%. Specifically, the mass percentage content of Ti can be 1.1%, 1.2%, 1.3%, or 1.4%, and the mass percentage content of Al can be 0.9%, 1.0%, 1.1%, or 1.2%. In the alloy, Al and Ti can form a γ' phase with Ni. At high temperatures, the γ' phase can hinder dislocation movement, thereby improving the high-temperature strength and creep resistance of the alloy.

[0041] In some embodiments of the present invention, the total mass percentage of Mo and Nb is 1.0% to 1.5%. Specifically, the total mass percentage of Mo and Nb can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, or 1.5%.

[0042] For example, the mass percentage content of Mo is 0.1%, and the mass percentage content of Nb can be 0.9%, 1.0%, 1.1%, or 1.2%.

[0043] The mass percentage content of Mo is 0.2%, and the mass percentage content of Nb can be 0.8%, 0.9%, 1.0%, 1.1%, or 1.2%.

[0044] The mass percentage content of Mo is 0.3%, and the mass percentage content of Nb can be 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, or 1.2%.

[0045] The mass percentage content of Mo is 0.4%, and the mass percentage content of Nb can be 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or 1.1%.

[0046] The mass percentage content of Mo is 0.5%, and the mass percentage content of Nb can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1.0%.

[0047] The mass percentage content of Mo is 0.6%, and the mass percentage content of Nb can be 0.5%, 0.6%, 0.7%, 0.8%, or 0.9%.

[0048] The mass percentage content of Mo is 0.7%, and the mass percentage content of Nb can be 0.5%, 0.6%, 0.7%, or 0.8%.

[0049] The γ' phase is the core of creep resistance. Mo and Nb will selectively dissolve into the γ' phase to form a more stable Ni3 (Al,Ti,Mo,Nb) solid solution. Mo can improve the dislocation cutting resistance of the γ' phase, and Nb can improve the high-temperature stability of the γ' phase.

[0050] A second aspect of the present invention provides a heat treatment method for the above-mentioned novel iron-nickel-based alloy material, comprising the following steps: Step 1: Solution Heat Treatment: The iron-nickel-based superalloy is heated and held at that temperature for a period of time before cooling. Solution heat treatment allows solid solution strengthening elements such as Cr and Mo to diffuse and dissolve in the matrix, forming a supersaturated solid solution. This means that the content of dissolved Ti, Al, Nb, Cr, and Mo in the matrix is ​​much higher than in the equilibrium state. The supersaturated solid solution provides sufficient precipitation elements for subsequent aging heat treatment, avoiding insufficient precipitation strengthening due to insufficient elements. Simultaneously, during the solution treatment process, the coarse grains in the cast state recrystallize into fine, uniform austenite grains. After grain refinement, the total area of ​​grain boundaries increases, and the sliding stress borne by individual grain boundaries is dispersed, directly reducing the grain boundary sliding rate. Furthermore, the refined grains provide more grain boundary nucleation sites for the precipitation of the second phase during subsequent aging heat treatment, promoting the uniform distribution of the second phase within the grains and at grain boundaries, further strengthening the grain boundaries.

[0051] Step 2, First Aging Heat Treatment: The iron-nickel-based superalloy after the solution heat treatment in Step 1 is heated and held at that temperature for a period of time before cooling. The first aging heat treatment causes Ti and Al atoms in the supersaturated solid solution to preferentially accumulate at matrix defects, forming the γ' phase. Simultaneously, Cr and C atoms at grain boundaries precipitate small amounts of fine carbides. These carbides pin the grain boundaries, reducing grain boundary vacancy migration and initially enhancing the grain boundary's anti-slip ability. At the same time, B and Zr grain boundary purifying elements further diffuse towards the grain boundaries, filling grain boundary vacancies and reducing grain boundary activity, laying the groundwork for grain boundary strengthening in the subsequent second aging heat treatment.

[0052] Step 3, Second Aging Heat Treatment: The iron-nickel-based superalloy after the first aging heat treatment in Step 2 is heated, held at that temperature for a period of time, and then cooled. The second aging heat treatment causes the γ' phase formed in the first aging to grow slowly, which can reduce the dislocation slip rate, while further precipitating new γ' phase. NbC nuclei grow synchronously, forming a synergistic pinning with the γ' phase. The γ' phase hinders intragranular dislocation movement, while NbC hinders grain boundary dislocation migration.

[0053] Existing single-aging techniques require prolonged high-temperature holding to precipitate a sufficient amount of the second phase, which easily leads to coarsening of the γ' phase. Coarsening of the γ' phase weakens grain boundaries, reduces sliding resistance, and diminishes resistance to negative creep. In contrast, the two-step aging heat treatment of this invention can strictly control the size of the γ' phase while ensuring the quantity of the second phase, thus ensuring that the γ' phase is not prone to coarsening during long-term high-temperature service.

[0054] In some embodiments of the present invention, in step one, the solution heat treatment process is carried out at a temperature of 1150 ℃-1190 ℃ and a holding time of 3~5 h. Specifically, the solution heat treatment temperature can be 1150 ℃, 1160 ℃, 1170 ℃, 1180 ℃, or 1190 ℃, and the holding time can be 3 h, 4 h, or 5 h. This ensures complete dissolution of the high-melting-point phase, forming a coarse γ' phase and coarse NbC in the as-cast state, and allows the Cr and Mo solid solution elements to fully diffuse into the matrix, forming a supersaturated solid solution.

[0055] In some embodiments of the present invention, in step two, the temperature of the first aging heat treatment process is 620 ℃-660 ℃, and the holding time is 20~30 h. Specifically, the temperature of the first aging heat treatment process can be 620 ℃, 630 ℃, 640 ℃, 650 ℃, or 660 ℃, and the holding time can be 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h, 29 h, or 30 h. The first aging heat treatment process can prevent Ti and Al from agglomerating and forming coarse cores. Nanoscale cores can significantly increase the number of nuclei, preferentially nucleating at matrix defects, ensuring uniform core distribution.

[0056] In some embodiments of the present invention, in step three, the temperature of the second aging heat treatment process is 795 ℃-835 ℃, and the holding time is 20~30 h. Specifically, the temperature of the second aging heat treatment process can be 795 ℃, 805 ℃, 815 ℃, 825 ℃, or 835 ℃, and the holding time can be 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h, 29 h, or 30 h. The second aging heat treatment process can provide sufficient energy for core growth and can strictly control the γ' phase growth rate. The long holding time ensures sufficient precipitation, optimizes grain boundary strengthening, and eliminates stress.

[0057] In some embodiments of the present invention, in step one, the iron-nickel-based superalloy is cooled by air or water. Air cooling and water cooling can suppress atomic diffusion and prevent premature precipitation of elements, allowing for sufficient precipitation during the subsequent two aging heat treatments.

[0058] If the cooling of the iron-nickel-based superalloy in step one is water cooling, the iron-nickel-based superalloy needs to be dried before proceeding to the next step.

[0059] In some embodiments of the present invention, in steps two and three, the iron-nickel-based superalloy is cooled by air. Compared with water cooling, air cooling has a lower cooling rate, which can quickly cool the alloy to room temperature, inhibiting core growth, and preventing the core atoms from dissolving or agglomerating.

[0060] A third aspect of the present invention provides a high-temperature component for an ultra-supercritical steam turbine, the high-temperature component being made of the aforementioned novel iron-nickel-based alloy material, and the high-temperature component being treated by the aforementioned heat treatment method.

[0061] In some embodiments of the present invention, the novel iron-nickel-based alloy material needs to be refined to form high-temperature components for ultra-supercritical steam turbines, i.e., to obtain an iron-nickel-based high-temperature alloy. Refining can reduce the content of harmful elements such as sulfur (S) and phosphorus (P), while also reducing the excessive dissolution of oxygen (O) and nitrogen (N). Elements such as sulfur (S) and phosphorus (P) preferentially accumulate at grain boundaries, forming low-melting-point eutectic phases. At high temperatures, grain boundaries lose their anti-slip ability due to the melting of the eutectic phase. After refining, the grain boundaries are free of low-melting-point phases, which can improve the grain boundary bonding force and thus suppress negative creep dominated by grain boundary slip.

[0062] The refining process for novel iron-nickel-based alloy materials involves sequential electric furnace melting, LF refining, VOD refining, and LF refining to obtain the iron-nickel-based high-temperature alloy. Electric furnace melting transforms the alloy raw material from a solid state into a homogeneous melt and initially controls the content of the main components. The electric furnace used is either an electric arc furnace or an induction furnace. The first LF refining process involves heating, stirring, and slag formation to make the melt more homogeneous and reduce impurities. LF refining is performed in a ladle refining furnace. VOD refining uses a vacuum environment and oxygen blowing to reduce gas content and stabilize carbon content. VOD refining is performed in a vacuum oxygen decarburization furnace. The second LF refining process is to compensate for minor defects after VOD refining, ensuring that the melt fully meets the requirements for subsequent casting and heat treatment.

[0063] In some embodiments of the present invention, the iron-nickel-based superalloy is heated in a vacuum heat treatment furnace. The high vacuum environment of the vacuum heat treatment furnace can reduce the oxygen content and decrease the contact between the alloy material and oxygen, thereby avoiding the formation of internal oxide inclusions and improving the purity of the iron-nickel-based superalloy.

[0064] This invention combines single-step solution heat treatment with two-step aging heat treatment to adapt to the compositional characteristics of novel iron-nickel-based high-temperature alloys. It achieves full-cycle control of the γ′ phase precipitation process, suppresses negative creep during the service of high-temperature alloys, avoids abnormal stress cycles, thermal fatigue, and mechanical fatigue caused by negative creep in structural components, inhibits the initiation and propagation of cracks in structural components, and improves the service safety and lifespan of high-temperature alloy castings.

[0065] This invention enables a novel iron-nickel-based high-temperature alloy to possess high high-temperature strength through a heat treatment process, allowing it to maintain good mechanical properties at high temperatures and withstand the dual effects of high temperature and stress. This meets the material strength requirements of high-temperature components in ultra-supercritical steam turbines at temperatures of 650°C and above, ensuring the structural stability of the cylinder valve housing at high temperatures and preventing deformation or damage due to insufficient strength.

[0066] The following detailed description of specific embodiments of the present invention, in conjunction with preferred embodiments, further illustrates the relevant details. When numerical ranges are given in the embodiments, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range, as well as any value between the two endpoints, may be selected. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by those skilled in the art. In addition to the specific methods, devices, and materials used in the embodiments, the present invention can be implemented using any prior art methods, devices, and materials similar to or equivalent to those described in the embodiments of the present invention, provided that those skilled in the art possess the prior art and the description of the present invention.

[0067] Example 1 A novel iron-nickel-based alloy material comprises the following components by mass percentage: C 0.042%, Si 0.15%, Zr 0.015%, Cr 16.4%, Mo 0.25%, Co 1.46%, Nb 0.66%, Ni 34.7%, Ti 1.42%, Al 1.26%, B 0.0025%, W 0.026%, N 0.00344%, Y 0.11%, balance Fe.

[0068] The aforementioned novel iron-nickel-based alloy material was successively processed by electric furnace melting, LF refining, VOD refining, and LF refining to obtain an iron-nickel-based high-temperature alloy.

[0069] The heat treatment method for the above-mentioned iron-nickel based superalloys includes the following steps: Step 1: Heat the iron-nickel-based superalloy to 1180℃ in a vacuum heat treatment furnace, hold for 3 hours, and then dry after water cooling.

[0070] Step 2: After completing Step 1, heat the iron-nickel-based superalloy to 650℃ in a vacuum heat treatment furnace, hold for 20 hours, and then air cool.

[0071] Step 3: After completing Step 2, heat the iron-nickel-based superalloy to 825℃ in a vacuum heat treatment furnace, hold for 20 hours, and then air cool.

[0072] Example 2 A novel iron-nickel-based alloy material comprises the following components by mass percentage: C 0.045%, Si 0.14%, Zr 0.019%, Cr 17.2%, Mo 0.38%, Co 1.33%, Nb 0.73%, Ni 36.2%, Ti 1.32%, Al 1.14%, B 0.0039%, W 0.056%, N 0.0044%, Y 0.12%, balance Fe.

[0073] The method for preparing the above-mentioned novel iron-nickel-based alloy material into an iron-nickel-based high-temperature alloy is the same as that in Example 1.

[0074] The heat treatment method for the above-mentioned iron-nickel based superalloys includes the following steps: Step 1: Heat the iron-nickel-based superalloy to 1160℃, hold for 3 hours, cool with water, and then dry.

[0075] Step 2: After completing Step 1, heat the iron-nickel-based superalloy to 630℃ in a vacuum heat treatment furnace, hold for 20 hours, and then air cool.

[0076] Step 3: After completing Step 2, heat the iron-nickel-based superalloy to 805℃ in a vacuum heat treatment furnace, hold it at that temperature for 20 hours, and then air cool it.

[0077] Comparative Example 1 The composition of the novel iron-nickel-based alloy material in this comparative example is the same as that in Example 1.

[0078] The method for preparing the novel iron-nickel-based alloy material into an iron-nickel-based high-temperature alloy in this comparative example is the same as that in Example 1.

[0079] The heat treatment method for the above-mentioned iron-nickel based superalloys includes the following steps: Step 1: Heat the iron-nickel-based superalloy to 1180℃ in a vacuum heat treatment furnace, hold for 3 hours, and then dry after water cooling.

[0080] Step 2: After completing Step 1, heat the iron-nickel-based superalloy to 800℃ in a vacuum heat treatment furnace, hold it at that temperature for 8 hours, and then air cool it.

[0081] Comparative Example 2 The composition of the novel iron-nickel-based alloy material in this comparative example is the same as that in Example 2.

[0082] The method for preparing the novel iron-nickel-based alloy material into an iron-nickel-based high-temperature alloy in this comparative example is the same as that in Example 1.

[0083] The heat treatment method for the above-mentioned iron-nickel based superalloys includes the following steps: Step 1: Heat the iron-nickel-based superalloy to 1160℃ in a vacuum heat treatment furnace, hold for 3 hours, cool with water, and then dry.

[0084] Step 2: After completing Step 1, heat the iron-nickel-based superalloy to 800℃ in a vacuum heat treatment furnace, hold it at that temperature for 8 hours, and then air cool it.

[0085] The components and heat treatment parameters of the above embodiments and comparative examples are shown in Table 1 below: Table 1. Components and heat treatment parameters for the examples and comparative examples Referring to GB / T 228.1-2021 "Metallic Materials - Tensile Testing", the plastic elongation strength Rp0.2, tensile strength Rm, elongation after fracture A, and reduction of area Z of the iron-nickel-based superalloy were tested at room temperature (RT), with the performance at room temperature (RT) used as a comparison. The tensile properties of the above examples and comparative examples are shown in Table 2 below.

[0086] The tensile creep and endurance tests of the metals were conducted in accordance with GB / T 20120.1-2006 "Metallic Materials - High Temperature Tensile Creep Test". The test results are as follows: Figure 1 and Figure 2 As shown.

[0087] Table 2 Tensile properties of the examples and comparative examples The iron-nickel-based superalloys in Example 1 and Comparative Example 1 have the same composition and the same solution heat treatment process. Example 1 uses a two-step aging heat treatment, with low-temperature long-time nucleation and medium-temperature long-time growth, while Comparative Example 1 uses a one-step aging heat treatment, with high-temperature short-time nucleation.

[0088] From room temperature to 700℃, the Rp0.2 of Example 1 (553~590MPa) and Rm (685~780MPa) are both higher than those of Comparative Example 1 (514~552MPa) and Rm (638~730MPa). In the high-temperature range of 600~700℃, the strength difference is even more pronounced. For example, at 700℃, the Rm of Example 1 is 685MPa, while the Rm of Comparative Example 1 is only 638MPa, a difference of 47MPa.

[0089] The A values ​​of Comparative Example 1 (10%–14.5%) and Z values ​​of Comparative Example 1 (12%–26%) are both lower than those of Example 1 (15.5%–21.5%) and Z values ​​of Comparative Example 1 (20%–32%). This indicates that plasticity at high temperatures is crucial for suppressing negative creep, and the superior plasticity of Example 1 demonstrates its stronger resistance to high-temperature deformation.

[0090] The one-step aging heat treatment in Comparative Example 1, with its high temperature and short time, resulted in coarsening of the γ' phase and carbides, allowing dislocations to easily bypass them, thus weakening the strengthening effect. Comparative Example 1, lacking a second aging heat treatment, failed to provide sustained strengthening due to the coarsened γ' phase and carbides from the one-step aging heat treatment.

[0091] In the first aging heat treatment of Example 1, the slow atomic diffusion at low temperature promotes the slow aggregation of elements such as Ti, Al, and Nb at matrix defects, forming a large number of nanoscale γ' phase cores. Simultaneously, ultrafine carbides, such as NbC, precipitate, laying the foundation for subsequent strengthening. In the second aging heat treatment of Example 1, the moderate temperature allows the nanocores formed in the first aging heat treatment to grow slowly and be uniformly distributed. The γ' phase hinders dislocation movement, while the carbides pin grain boundaries, inhibiting grain boundary sliding. Both work synergistically to enhance resistance to high-temperature deformation.

[0092] The conclusions drawn from comparing Example 2 and Comparative Example 2 are consistent with the conclusions drawn from comparing Example 1 and Comparative Example 1 above.

[0093] In summary, under the premise of the same composition and solution heat treatment process, two-step aging heat treatment can improve the high-temperature strength and plasticity of iron-nickel-based superalloys compared with one-step aging heat treatment, and suppress negative creep inducers such as grain boundary sliding and dislocation movement at the microstructure level, ultimately achieving better resistance to high-temperature negative creep performance.

[0094] like Figure 1 As shown, the heat-treated iron-nickel-based superalloys from Example 1 and Comparative Example 1 were subjected to tensile creep and endurance tests at a temperature of 650°C and a stress of 100 MPa, yielding the measured creep curves. The iron-nickel-based superalloy in Comparative Example 1 exhibited significant negative creep, which did not improve even after prolonged service. The iron-nickel-based superalloy in Example 1 only showed short-term negative creep within 600 hours and did not exhibit negative creep after prolonged service. This indicates that the process improved the negative creep phenomenon of the iron-nickel-based superalloy.

[0095] like Figure 2 As shown, the heat-treated iron-nickel-based superalloys from Examples 2 and 2 were subjected to tensile creep and rupture tests at a temperature of 650°C and a stress of 200 MPa, yielding the measured creep curves. The iron-nickel-based superalloy in Comparative Example 2 exhibited significant negative creep, which did not improve after prolonged service. The iron-nickel-based superalloy in Example 2 did not exhibit negative creep after prolonged service. This indicates that the process improved the negative creep phenomenon in the iron-nickel-based superalloy.

[0096] This invention combines single-step solution heat treatment with two-step aging heat treatment to adapt to the compositional characteristics of novel iron-nickel-based high-temperature alloys. It achieves full-cycle control of the γ′ phase precipitation process, suppresses negative creep during the service of high-temperature alloys, avoids abnormal stress cycles, thermal fatigue, and mechanical fatigue caused by negative creep in structural components, inhibits the initiation and propagation of cracks in structural components, and improves the service safety and lifespan of high-temperature alloy castings.

[0097] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. A novel iron-nickel-based alloy material, characterized in that, Includes the following components by mass percentage: C 0.03%~0.06%, Si ≤0.2%, Zr ≤0.05%, Cr 16.0%~18.0%, Mo ≤0.9%, Co 1.2%~1.7%, Nb 0.5%~1.2%, Ni 33%~39%, Ti 1.0%~1.5%, Al 0.8%~1.5%, B ≤0.005%, W ≤0.7%, N ≤0.01%, Y 0.1%~0.15%, balance Fe and unavoidable impurities.

2. The novel iron-nickel-based alloy material according to claim 1, characterized in that, Includes one or more of the following characteristics: (a) The mass percentage of C is 0.03% to 0.05%; (b) The mass percentage of Cr is 16.5% to 17.5%; (c) The mass percentage of Mo is ≤0.7%; (d) The mass percentage of Nb is 0.5% to 1.2%; (e) The mass percentage of Ni is 35% to 37%; (f) The mass percentage of Ti is 1.1% to 1.4%; (g) The mass percentage of Al is 0.9% to 1.2%.

3. The novel iron-nickel-based alloy material according to claim 1, characterized in that, The total mass percentage of Mo and Nb is 1.0% to 1.5%.

4. A heat treatment method for the novel iron-nickel-based alloy material as described in any one of claims 1-3, characterized in that, Includes the following steps: Step 1, Solution heat treatment: Heat the iron-nickel-based superalloy to 1150 ℃-1190 ℃, hold it at that temperature for 3~5 h, and then cool it. Step 2, First aging heat treatment: The iron-nickel-based superalloy after solution heat treatment in Step 1 is heated to 620℃-660℃ and held at that temperature for 20~30 h before cooling. Step 3, Second aging heat treatment: The iron-nickel-based superalloy after the first aging heat treatment in Step 2 is heated to 795 ℃-835 ℃ and held at that temperature for 20~30 h before cooling.

5. The heat treatment method for the novel iron-nickel-based alloy material according to claim 4, characterized in that, In step one, the solution heat treatment temperature is 1180 ℃ and the holding time is 3 h.

6. The heat treatment method for the novel iron-nickel-based alloy material according to claim 4, characterized in that, In step two, the temperature of the first aging heat treatment is 650 ℃, and the holding time is 20 h.

7. The heat treatment method for the novel iron-nickel-based alloy material according to claim 4, characterized in that, In step three, the temperature of the second aging heat treatment is 825 ℃, and the holding time is 20 h.

8. The heat treatment method for the novel iron-nickel-based alloy material according to claim 4, characterized in that, Includes one or more of the following characteristics: (a) In step one, the iron-nickel-based superalloy is cooled by air or water; (b) In step two, the iron-nickel-based superalloy is cooled by air cooling; (c) In step three, the iron-nickel-based superalloy is cooled by air cooling.

9. The heat treatment method for the novel iron-nickel-based alloy material according to claim 4, characterized in that, The iron-nickel-based superalloy is heated in a vacuum heat treatment furnace.

10. A high-temperature component for an ultra-supercritical steam turbine, characterized in that, The high-temperature component is made of the novel iron-nickel-based alloy material according to any one of claims 1-3, and the high-temperature component is treated by the heat treatment method according to any one of claims 4-9.